A randomized, double‐blind, crossover, placebo‐controlled comparative clinical trial of arginine aspartate plus adenosine monophosphate for the intermittent treatment of male erectile dysfunction. (26th December 2012) - Neuzillet, Y.; Hupertan, V.; Cour, F.; Botto, H.; Lebret, T.
Summary Efficacy and safety of l‐arginine aspartate 8 g combined with 200 mg of adenosine monophosphate (AA) with placebo (PL) alone for intermittent treatment of mild‐to‐moderate erectile dysfunction (ED) were compared. The study design was a double‐blind, PL‐controlled, two‐way crossover randomized clinical trial with 26 patients. Efficacy was assessed by International Index of Erectile Function (IIEF) and two additional validated questionnaires [the Erection Hardness Score (EHS) and the Erectile Dysfunction Inventory of Treatment Satisfaction (EDITS). During each crossover period, separated by a 2‐week wash‐out period, drugs were administered orally, 1–2 h before sexual intercourse. Primary endpoint was a change in the IIEF. Secondary endpoints were patient and investigator assessments of treatment success. Investigators' and patients' assessment of efficacy was significantly improved by the combination vs. PL (p = 0.01 and p = 0.04 respectively]. EHS and EDITS questionnaires were both improved by the combination (p = 0.015 and p = 0.017 respectively). There was no significant difference in terms of tolerance between AA and PL or severe adverse events. ED patients demonstrated significant improvements in all IIEF domains with the exception of the Sexual Desire and Orgasmic Domains when treated with AA compared with PL. This pilot phase II study showed that the on‐demand oral administration at a high dosage of l‐arginine aspartate–adenosine monophosphate combination may be effective in patients with mild‐to‐moderate ED, is very well tolerated and could be tested as a safe first‐line therapy in a larger size phase III study.